Aplikasi Akuntansi Penentuan Sewa Alat Berat PT. Mitra Mandiri Transindo Menggunakan Metode Activity Based Costing Berbasis Web - sukemi Kamto Sudibyo; Ahmad Ashifuddin Aqham; Aliveia Orenzia (Universitas Sains dan Teknologi Komputer, 2020)
At PT. Mitra Mandiri Transindo, in the process of recording the determination of heavy equipment leasing, is still done manually using note documents which can cause errors in the heavy equipment rental determination transaction. This has resulted in problems in making reports which can take longer. Accounting application for determining heavy equipment leases at PT. Mitra Mandiri Transindo uses the activity based costing method to make it easier for PT. Mitra Mandiri Trasindo in the data management process of determining the total heavy equipment rental and creating reports that are faster, more precise and accurate on a web-based basis. With the implementation of accounting applications for determining heavy equipment leases at PT. Mitra Mandiri Transindo using the web-based Activity Based Costing method also has the following benefits: (1) It can be seen what lease transactions and costs are needed quickly, precisely and accurately. (2) Producing appropriate reports that can be used as a basis for making decisions by the Director of PT. Mitra Mandiri Transindo.